Self-assembled phosphate-polyamine networks as biocompatible supramolecular platforms to modulate cell adhesion - Muzzio, Nicolás Eduardo (2018)
The modulation of cell adhesion via biologically inspired materials plays a key role in the development of realistic platforms to envisage not only mechanistic descriptions of many physiological and pathological processes but also new biointerfacial designs compatible with the requirements of biomedical devices. In this work, we show that the cell adhesion and proliferation of three different cell lines can be easily manipulated by using a novel biologically inspired supramolecular coating generated via dip coating of the working substrates in an aqueous solution of polyallylamine in the presence of phosphate anions - a simple one-step modification procedure. Our results reveal that selective cell adhesion can be controlled by varying the deposition time of the coating. Cell proliferation experiments showed a cell type-dependent quasi-exponential growth demonstrating the nontoxic properties of the supramolecular platform. After reaching a certain surface coverage, the supramolecular films based on phosphate-polyamine networks displayed antiadhesive activity towards cells, irrespective of the cell type. However and most interestingly, these antiadherent substrates developed strong adhesive properties after thermal annealing at 37 °C for 3 days. These results were interpreted based on the changes in the coating hydrophilicity, topography and stiffness, with the latter being assessed by atomic force microscopy imaging and indentation experiments. The reported approach is simple, robust and flexible, and would offer opportunities for the development of tunable, biocompatible interfacial architectures to control cell attachment for various biomedical applications.